The Effect of Four Months of Detraining Following Eight Months of Corrective Exercises on Lumbar Lordosis of Schoolgirls - Neda Rezvankhah; Mohammad Hossein Alizadeh; Mohammad reza Kordi (The Society of Aging and Physical Activity (SAPA), 2013)
The purpose of the present research is to study the effect of 4 months of detraining following 8 months of corrective exercises on lumbar lordosis of schoolgirls after maturity.The subjects were the girls having the increased lordosis in while they were in the 5th stage of tanner and fell into the experimental group (n=16) and the control group (n=16). The experimental group participated in corrective exercises program for 8 weeks. The lumbar lordosis was checked before and 8 weeks after the corrective exercises and it was clarified that those having the lumbar lordosis were healed. Then, 4 months of detraining were applied and rechecking was finally done.The findings show that 4 months of detraining following 8 months of corrective exercises lead to increase lumbar lordotic mean angle in the experimental group in comparison with the control group (p<0.05). The observations indicate that although corrective exercises were effective on healing the lumbar lordosis of mature schoolgirls, 4 months of detraining let it be back. So, the subjects are required to participate in a continual program including corrective exercises in order to maintain the effect of the exercises, and this program is not to be abandoned after observing the desired results. Hence, correcting the lifestyle which is effective on the emergence of lumbar lordosis should be taken into account.